Cryptography as a Service (CaaS): Quantum cryptography for secure cloud computing - Olanrewaju, Rashidah Funke; Islam, Thouhedul; Khalifa, Othman Omran; Anwar, Farhat; Pampori, Bisma Rasool (The Indian Society of Education and Environment, 2017)
Cloud Computing is an emerging technology nowadays. Due to the accessibility, availability, and cost effectiveness, cloud computing has became essential computing system in both, private and public sectors. However, secure data transfer is still a big question where transferring link between user and server are not stabilized yet. As a result, many cloud users lost their valuable data. However, this paper proposes as integrated service of Advanced Quantum Cryptography with Cloud Computing. To ensure the secure Cloud Environment between sender and receiver, Quantum Cryptography proposes the use of photons and physics to generate cryptographic keys.